2018
DOI: 10.1002/jcb.28111
|View full text |Cite
|
Sign up to set email alerts
|

A panel of noncoding RNAs in non–small‐cell lung cancer

Abstract: Non–small‐lung cancer (NSCLC) is the leading cause of cancer death. Early detection of NSCLC could pave the way for effective therapies. Analysis of molecular genetic biomarkers in biological fluids has been proposed as a useful tool for cancer diagnosis. Here, we aimed to develop a panel of noncoding RNAs (ncRNAs) in sputum for NSCLC early detection. Expression of 11 ncRNAs were analyzed by real–time polymerase chain reaction in sputum samples of 30 NSCLC patients and 30 sex‐ and age‐matched cancer‐free contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 71 publications
0
35
0
1
Order By: Relevance
“…In this period, 12 studies were excluded because they are reviews or meta-analyses (n=5), insu ciency information (n=3), detecting miRNA methylation (n=2) or data overlapping (n=2). As a result, 16 articles 11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] were eligible for nal meta-anlaysis. Figure 1A showed the process of studies identi cation.…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this period, 12 studies were excluded because they are reviews or meta-analyses (n=5), insu ciency information (n=3), detecting miRNA methylation (n=2) or data overlapping (n=2). As a result, 16 articles 11,13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] were eligible for nal meta-anlaysis. Figure 1A showed the process of studies identi cation.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…These studies published from 2010 to 2018, and the sample size ranged from 30 to 315. Two studies conducted in Asian 24,27 , seven studies conducted in Caucasian 13,20,25,[28][29][30][31] and the remaining seven studies 11,19,[21][22][23]26,32 conducted in mixed population. Two studies 19,26 selected healthy population as controls, 11 studies 13,20-23,25,28-32 selected cancer-free subjects as controls, and the remaining three studies 11,24,27 applied benign pulmonary disease (BPD) as controls.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…For example, we have shown that downregulations of miR‐486‐5p contribute to the development of NSCLC by regulating Pim‐1 and ARHGAP5 . We and others have also demonstrated that aberrant miRNA expressions detected in sputum biologically reflect those in primary lung cancer . We have recently developed a panel of two sputum miRNA (miR‐31‐5p and miR‐210‐3p) biomarkers for NSCLC with 65% sensitivity and 89% specificity .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] We and others have also demonstrated that aberrant miRNA expressions detected in sputum biologically reflect those in primary lung cancer. [9][10][11][12][13][14][15] We have recently developed a panel of two sputum miRNA (miR-31-5p and miR-210-3p) biomarkers for NSCLC with 65% sensitivity and 89% specificity. 16 Furthermore, efforts have been made to develop cell-free (eg, plasma) biomarkers by detecting the circulating molecules directly released from lung tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Various microRNAs play key roles in LC pathogenesis and have the potential to be therapeutically targeted molecules and diagnostic markers. Therefore, investigation of the role of microRNA molecules may lead to an improved understanding of lung carcinogenesis and shed light on the therapeutic strategies and effective diagnostic to manage LC …”
Section: Introductionmentioning
confidence: 99%